Isolation, Antimicrobial Resistance Phenotypes, and Virulence Genes of Bordetella bronchiseptica From Pigs in China, 2018–2020 - Zhang, Yue; Yang, Hao; Guo, Long; Zhao, Mengfei; Wang, Fei; Song, Wenbo; Hua, Lin; Wang, Lei; Liang, Wan; Tang, Xibiao; Peng, Zhong; Wu, Bin (Frontiers in Veterinary Science, 2021)
Bordetella bronchiseptica is a leading cause of respiratory diseases in pigs. However, epidemiological data of B. bronchiseptica in pigs particularly in China, the largest pig rearing country in the world is still limited. We isolated 181 B. bronchiseptica strains from 4259 lung samples of dead pigs with respiratory diseases in 14 provinces in China from 2018 to 2020. The average isolation rate of this 3-year period was 4.25% (181/4259). Antimicrobial susceptibility testing performed by disc diffusion method revealed that most of the B. bronchiseptica isolates in this study were resistant to ampicillin (83.98%), while a proportion of isolates were resistant to cefotaxime (30.39%%), chloramphenicol (12.71%), gentamicin (11.60%), florfenicol (11.60%), tetracycline (8.84%), amoxicillin (8.29%), tobramycin (6.63%), ceftriaxone (4.97%), and cefepime (0.55%). There were no isolates with resistant phenotypes to imipenem, meropenem, polymyxin B, ciprofloxacin, enrofloxacin, and amikacin. In addition, ~13.18% of the isolates showed phenotypes of multidrug resistance. Detection of antimicrobial resistance genes (ARGs) by PCR showed that 16.57% of the B. bronchiseptica isolates in this study was positive to aac(3)-IV, while 3.87%, 2.21%, 1.10%, 0.55%, 0.55%, and 0.55% of the isolates were positive to aac6'-Ib, rmtA, blaTEM, blaSHV, oqxB, and tetA, respectively. Detection of virulence factors encoding genes (VFGs) by conventional PCR showed that over 90% of the pig B. bronchiseptica isolates in this study were positive to the five VFGs examined (fhaB, 97.24%; prn, 91.16%; cyaA, 98.34%; dnt, 98.34%; betA, 92.82%). These results demonstrate B. bronchiseptica as an important pathogen associated with pig respiratory disorders in China. The present work contributes to the current understanding of the prevalence, antimicrobial resistance and virulence genes of B. bronchiseptica in pigs.